S187. Cerebral oxygen saturation and cytochrome oxidase redox state in children with epilepsy: A pilot study - MULTICHANNEL NIRS for epilepsy seizure detection. (May 2018) - Sannagowdara, Kumar; Malloy, Marsha; Chen, Wei-Liang; Quirk, Brendan; Kadamati, Parvati; Sugar, Jeffrey; Ranji, Mahsa; Monrad, Priya; Brown, Jennifer; Whelan, Harry
Abstract : Introduction: Epilepsy remains a significant healthcare problem associated with significant morbidity and mortality. Electroencephalograms (EEGs) provide a means of identifying ongoing seizures. However, specialized equipment is needed to obtain and interpret data. There remains a need for technologies that are easily utilized and interpreted for the purpose of monitoring children in the time periods before, during and after seizure activity. NIRS cerebral oximetry works as a noninvasive measurement that allows continuous measurement of cerebral oxygen availability. This monitor serves as a surrogate to invasive measures of venous pO2, often obtained from the jugular vein to estimate cerebral oxygen levels. We recently published NIRS-EEG data with a limited number of NIRS probes in four patients with medically refractory epilepsy undergoing pre-surgical evaluation with ages ranging from 5 to 17 years. The purpose of this pilot study is to describe the relationship of regional cerebral oximetry and cytoximetry, measured using MULTICHANNEL NIRS (near-infrared spectroscopy) in the peri-ictal period in children with epilepsy. The hypothesis is: 1. Regional cerebral saturation of oxygen and/or cytochrome oxidase redox state will increase prior to the onset of seizure activity; 2. Regional cerebral saturation of oxygen and/or cytochrome oxidase redox state will have a varied response during seizure activity depending on the seizure type; 3. Regional cerebral saturation of oxygen and/or cytochrome oxidase redox state will return to baseline following cessation of seizure activity. Methods: The three goals for the research study are to: 1. Quantify the magnitude and direction of change of cerebral oxygen saturation and cytochrome oxidase redox state during the peri-ictal period in children with epilepsy; 2. Quantify the temporal relationship, magnitude and direction of change of cerebral oxygenation and cytochrome oxidase redox state in relationship to seizure type; 3. Measure the association of cerebral oxygenation and cytochrome oxidase redox state with systemic oxygen saturation, EEG findings and clinical status. Study subjects will include pediatric patients from birth to 18 years of age with a known seizure disorder who are being admitted to the epilepsy monitoring unit (EMU) or the ICU at CHW for further workup or medication management of their epilepsy. Children will be monitored per standard of care for the duration of their hospitalization, which typically is 3–5 days with the additional NIRS-EEG array added to their monitoring. Results: Preliminary data shows varied regional cerebral oxygen saturation and/or cytochrome oxidase redox state during interictal period and seizure activity depending on the seizure type. The increased blood flow clearly coincided with epileptiform activity and continued to increase as the epileptiform activity built up. Conclusion: Regional cerebral oxygen saturation increased in the epileptogenic focus, perhaps due to loss of cerebrovascular autoregulation.